2020
DOI: 10.3897/bdj.8.e50775
|View full text |Cite
|
Sign up to set email alerts
|

Standardised spider (Arachnida, Araneae) inventory of Lammi, Finland

Abstract: In June 2019, an ecology field course of the University of Helsinki was held at Lammi Biological Station, Southern Finland. Within this course, the students familiarised themselves with field work and identification of spiders and explored the diversity of species in the area. Three sampling plots were chosen, one in grassland and two in boreal forest, to demonstrate the sampling techniques and, by applying a standardised protocol (COBRA), contribute to a global spider biodiversity project. The colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…Immature specimens represented 59% of all the captured specimens on average, ranging between 39% -76% per plot. This result is similar to those obtained in other studies (Soukainen et al, 2020, Malumbres-Olarte et al, 2020a, Malumbres-Olarte et al, 2019Cardoso et al 2004;Russell-Smith & Stork 1995, Silva 1996, which ranged from 40% to 70%, and offers a first insight on the relevance of juvenile stages in spider inventories and the conclusions derived from them.…”
Section: An Important Component Of Biodiversity At a Given Time Is Mostly Represented By Juvenilessupporting
confidence: 91%
See 1 more Smart Citation
“…Immature specimens represented 59% of all the captured specimens on average, ranging between 39% -76% per plot. This result is similar to those obtained in other studies (Soukainen et al, 2020, Malumbres-Olarte et al, 2020a, Malumbres-Olarte et al, 2019Cardoso et al 2004;Russell-Smith & Stork 1995, Silva 1996, which ranged from 40% to 70%, and offers a first insight on the relevance of juvenile stages in spider inventories and the conclusions derived from them.…”
Section: An Important Component Of Biodiversity At a Given Time Is Mostly Represented By Juvenilessupporting
confidence: 91%
“…Thus, in most inventories and diversity studies immature stages are discarded during sorting. However, immature specimens may account for between 40% and 70% of the collected specimens in biodiversity surveys (Soukainen et al, 2020, Malumbres-Olarte et al, 2020a, Malumbres-Olarte, Cardoso, & Crespo, 2019Cardoso, Silva, Oliveira, & Serrano, 2004;Russell-Smith & Stork 1995, Silva 1996, or even up to 94% in extreme cases (Kuntner & Baxter, 1997). Disregarding immatures may significantly influence the inference of the temporal and spatial patterns of biodiversity, so their incorporation is desirable to obtain reliable estimates of diversity in short-term sampling protocols (Toti, Coyle, & Miller, 2000;Sorensen, Coddington, & Scharff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, this study demonstrated the value of utilizing student groups for sampling arthropods using a standardised protocol to generate biodiversity data, supporting recent studies on spiders (e.g. Cardoso et al 2017;Kiljunen et al 2020;Soukainen et al 2020). The data generated can be utilised to elucidate patterns in biodiversity between different biotopes and sampling years, and also facilitates comparison of the efficacy of different sampling methods by students.…”
Section: Discussionsupporting
confidence: 78%
“…Data generation for various organismal groups benefits greatly from the involvement of volunteers (Lovell et al 2010;Lewandowski and Specht 2015), citizen scientists (Theobald et al 2015;Chandler et al 2016) or students (e.g. Cardoso et al 2017;Kiljunen et al 2020;Soukainen et al 2020;Supriatna et al 2020) to assist with field sampling. Further, the extraction of nontarget groups as bycatch in surveys can also provide data that is comparable to dedicated surveys of those particular non-target groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in most inventories and diversity studies immature stages are discarded during sorting. However, immature specimens may account for between 40% and 70% of the collected specimens in biodiversity surveys (Cardoso et al, 2004; Malumbres‐Olarte, Boieiro, et al, 2020; Malumbres‐Olarte et al, 2019; Russell‐Smith & Stork, 1995; Silva, 1996; Soukainen et al, 2020), or even up to 94% in extreme cases (Kuntner & Baxter, 1997). Disregarding immatures may significantly influence the inference of the temporal and spatial patterns of biodiversity, so their incorporation is desirable to obtain reliable estimates of diversity in short‐term sampling protocols (Sørensen et al, 2002; Toti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%